Comparative study of procedures of de-functionalization of intestinal loops in omega - Bonilla, Conrado; Pressa, Carlos; Ressia, Oscar; Fernández, Miguel A. (Cirugía del Uruguay, 1975)
This is an experimental work in 28 dogs in which the authors study different constriction techniques of the afferent limb of an intestinal loop aiming to achieve a complete defunctionalization of it. Radiologic and necropsic studies show the early recovery of the patency of the bowel or they point out the danger of parietal necrosis with the use of certain materials. It is concluded that all of these techniques prove to fail in serving far their purpose.